Online professional development for teachers - Vrasidas, Charalambos; Glass, Gene V., 1940- (Current perspectives on applied information technologies., 2004)
How can professional development for teachers be more efficient and effective? This essential question lies at the heart of this timely and useful book. In an era marked by a heightened emphasis on school reform, the education and professional development of teachers is widely regarded as the keystone to educational improvement. Recently a bewildering array of online professional development programs has arisen. But how effective are these programs and how do they compare with one another? Inspired by a recent conference on usable knowledge at the Harvard Graduate School of Education, this book offers clear and practical answers to these and other questions about online professional development. The authors look closely at exemplary online programs, compare them carefully with one another, and draw helpful conclusions about themâboth for those who develop online programs, and for teachers and administrators in search of professional development programs that make a difference.